2022
DOI: 10.3390/ani12243485
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes in the Distribution and Abundance of Nine Deep-Water Skates (Arhynchobatidae: Rajiformes: Chondrichthyes) in the Northwestern Pacific

Abstract: Based on the analysis of long-term data from bottom trawl surveys (1977–2021), changes in the spatial distribution, position of the boundaries of the ranges and the catch rates of the nine most common deep-sea skates of the genus Bathyraja in the Russian waters of the Northwestern Pacific (B. violacea, B. aleutica, B. matsubarai, B. maculata, B. bergi, B. taranetzi, B. minispinosa, B. interrupta, and B. isotrachys) are considered. During the surveyed period, significant changes in the spatial distribution were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They also may be profitably marketed in Japan and Korea. In waters of the Russian Far East, 11.4–11.7 Kt were recommended for harvesting in the 1990s, 7.2–11.9 Kt in the 2000s, 11.2–14.0 Kt in the 2010s, and 11.2–11.3 Kt in the 2020s [ 13 ]. Since the fishing of deep-water skates, including the Aleutian skate, is currently developing in the North Pacific, an important role in their management should consider regular stock assessments and monitoring of the populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also may be profitably marketed in Japan and Korea. In waters of the Russian Far East, 11.4–11.7 Kt were recommended for harvesting in the 1990s, 7.2–11.9 Kt in the 2000s, 11.2–14.0 Kt in the 2010s, and 11.2–11.3 Kt in the 2020s [ 13 ]. Since the fishing of deep-water skates, including the Aleutian skate, is currently developing in the North Pacific, an important role in their management should consider regular stock assessments and monitoring of the populations.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing for skates in the North Pacific is still poorly developed, but quite promising [ 10 , 11 ]. Their biomass within Russian waters only amounts to about 677 thousand tons [ 12 ], but in some areas skates make up as much as 10% of the total groundfish biomass, and their abundance has increased markedly in recent years [ 13 ]. Technological studies have shown that the meat of skates contains almost a complete set of essential amino acids and is highly suitable for food production [ 14 ].…”
Section: Introductionmentioning
confidence: 99%